Om Agriculturstatistikens Vigtighed og Standpunkt hos os. (Foredrag, den 18de Marts 1857). - David, C. R. (Tidsskrift for Landøkonomi, 2018)
Om Agriculturstatistikens Vigtighed og Standpunkt hos os. (Foredrag, den 18de Marts 1857).